Od przedmiotu do podmiotu. Status dziecka w rodzinie i społeczeństwie - Golus, Anna (Wydawnictwo Naukowe UAM, 2018)
The status of children in family and society is low since the year dot. This state of things is caused especially by adultcentrism, which means the view on youngsters from adult perspective, including the belief that adulthood is normality and standard, whereas childhood is state of incompleteness and imperfection. The article discusses the roots of adultcentric notions, instrumental treatment and social exclusion of children. The author examines the changes in social status of children and the influenceof consumerism and information revolution on contemporary role of children in family and society. She also considers why the objectification of children is so difficult to end.
From Object to Subject. The Status of Children in Family and Society
Keywords: adultcentrism; children’s social status; children’s subjectivity; objectification of childre